Gambaran perilaku masyarakat terhadap pencegahan COVID-19 di Kecamatan Amurang - Ang Lucia Baguna; Iyone E. T. Siagian; Dina V. Rombot (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2021)
Background: The Corona Virus Disease (COVID-19) pandemic has spread to various countries in the world, including Indonesia. In response to this, the Indonesian government makes policies and regulations to control and prevent COVID-19. To ensure success in controlling and preventing COVID-19, community compliance is very important, which is largely influenced by the knowledge, attitudes, and actions of the community.Objective: To describe the behavior of the community towards the prevention of COVID-19 in Amurang District.Methods: This research is descriptive with a cross-sectional or cross-sectional design, which will be conducted in September-November 2021. Using the simple random sampling method, 110 respondents met the inclusion and exclusion criteria.Results and Conclusion: The level of knowledge of the people in Amurang District about COVID-19 in the good category is 87 people (79.1%), the attitude of the people in Amurang District about COVID-19 in the good category is 81 people (73.6%), and community actions in the Amurang District Amurang numbered 91 people (82.7%).Keywords: Knowledge, Attitude, Action, COVID-19